PID Controller for DC-DC Converter under Dynamic Load Change in Photovoltaics based Low-Voltage DC Microgrid - Setiawan, Made Andik; Hidayat, Fahmi; Sari, Ela (Universitas Muhammadiyah Malang, 2023)
Today, DC Microgrid gain more attraction due to increasing electronic digital devices application such smart-phones, smart-tvs, and other digital apparatus which are operated in DC form. In the common grid, the electric power from AC source is converted to DC voltage for powering the digital devices as load. Hence, there are power conversions from AC-DC and potentially loss energy during conversions. DC Microgrid consisted of sources, loads, distribution lines and energy storages. In small capacity DC Microgrid, the stability of the system is vulnerable by dynamic load change. During load demands fluctuations, the DC Microgrid voltage is also dynamically fluctuated and can reach over the designated rate. To solve this problem, the PID controller is introduced in the DC-DC converter for maintaining the voltage rate at designated value regardless the load demands. In this paper, the DC Microgrid is consisted of photovoltaics as DC sources, XL-6019 as DC-DC converter, Arduino as controller, voltage and current sensors, distribution lines and loads. The proposed method is evaluated via experimental results. The responses of the proposed method in the DC Microgrid system are presented, evaluated, discussed, and compared between with and without applied method. The experimental results indicate that the proposed method has ability to reduce the voltage profile fluctuations during load demands changes and in short time.